1994
DOI: 10.1073/pnas.91.21.9861
|View full text |Cite
|
Sign up to set email alerts
|

Molecules vs. morphology in avian evolution: the case of the "pelecaniform" birds.

Abstract: The traditional avian Order Pelecaniformes is composed of birds with all four toes connected by a web. This "totipalmate" condition is found in ca. 66 living species: 8 pelicans (Pelecanus), 9 boobies and gannets (Sula, Papasula, Morus), ca. 37 cormorants (Phalacrocorax), 4 anhingas or darters (Anhinga), 5 frigatebirds (Fregata), and 3 tropicbirds (Phaethon). Several additional characters are shared by these genera, and their monophyly has been assumed since the beginning of modern zoological nomenclature. Mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 18 publications
(13 reference statements)
3
75
0
3
Order By: Relevance
“…The Kishino-Hasegawa test did not indicate a significant difference between the best maximum-likelihood tree and the maximum-likelihood tree that includes all of the scDNA hybridization constraints. Our study falls in line with others where DNA hybridization and DNA sequence results are in general agreement (31,32).…”
Section: Discussionsupporting
confidence: 81%
“…The Kishino-Hasegawa test did not indicate a significant difference between the best maximum-likelihood tree and the maximum-likelihood tree that includes all of the scDNA hybridization constraints. Our study falls in line with others where DNA hybridization and DNA sequence results are in general agreement (31,32).…”
Section: Discussionsupporting
confidence: 81%
“…This implies the absence of major bottlenecks due to selection or chance effects, and is perhaps an argument for pleiotropy and against rapid convergence. Hedges & Sibley (1994) suggested that when, as here, molecular data produce a robust phylogeny that conflicts with morphology, the morphological characters should be reassessed. Perhaps a detailed morphological study (pace Strauch 1978) would reveal that similarity between the Pomarine skua, S. pomarinus, and other Stercorarius species is only skin-deep.…”
Section: Discussionmentioning
confidence: 99%
“…Ptilopachus is outside Phasianidae, as sister group to Odontophoridae; Alectura is nested within Aepypodius; complex rearrangements within Phasianidae (88-110) Anseriformes Dendrocygna, Bucephala and Nettapus are paraphyletic; many deeper branches remain unresolved (97,109,(111)(112)(113)(114)(115)(116) (66,67,87,(135)(136)(137)(138)(139)(140)(141)(142)(143)(144)(145) …”
Section: Galliformesmentioning
confidence: 99%
“…Major taxonomic changes relative to (38) and clade-specific references for source trees Palaeognathae no major taxonomic change (82)(83)(84)(85)(86)(87) …”
Section: Cladementioning
confidence: 99%